Combinatorial inkjet printing for compositional tuning of metal-halide perovskite thin films. Issue 9 (10th February 2022) - Näsström, Hampus; Shargaieva, Oleksandra; Becker, Pascal; Mathies, Florian; Zizak, Ivo; Schröder, Vincent R. F.; List-Kratochvil, Emil J. W.; Unold, Thomas; Unger, Eva
Abstract : A new method for droplet placement in combinatorial inkjet printing, validated by synchrotron micro-spot X-ray diffraction mapping of CsPb(Br x I1− x )3 . Abstract : To accelerate the materials discovery and development process for a sustainable technology advancement it is imperative to explore and develop combined high-throughput material synthesis and analysis workflows. In this work, we investigate a method of combinatorial inkjet-printing to tune the composition of the inorganic cesium lead mixed halide perovskite solid solution, CsPb(Br x I1− x )3 . The compositional variation is achieved by simultaneous printing of different precursor inks with multiple printheads and controlled by varying the number of droplets printed by each printhead throughout the sample. The droplet placement is optimised through an algorithm that allows maximum mixing of the combined inks. The local compositional homogeneity of thin-film samples was investigated as a function of the printing resolution by micrometer-resolution X-ray fluorescence and synchrotron-based grazing-incidence wide-angle X-ray scattering. We show that a combinatorial library of ten compositions between CsPbI3 and CsPbBr2 I, printed using the developed algorithm, is locally homogeneous for the optimised printing parameters. An implementation of the algorithm in the high-level programming language Python is provided for easy use in other systems.